2006
DOI: 10.2527/2006.8461362x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of utilizing ileal digestible lysine and threonine for whole body protein deposition in growing pigs is reduced when dietary casein is replaced by wheat shorts1,2

Abstract: To determine the effect of dietary inclusion level of wheat shorts (WS; a high nonstarch poly-saccharide-containing feed ingredient) and casein (CS; a control) on the efficiency of utilizing ileal digestible Lys (kLys) and Thr (kThr) for whole body protein deposition (PD) in the growing pig, 2 separate N-balance studies were conducted with either Lys or Thr as first-limiting AA in cornstarch-based diets. For the Lys study, a basal diet (L-basal) was formulated to contain 0.24 g of standardized ileal digestible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
15
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
9
15
0
3
Order By: Relevance
“…This means that 10% of the absorbed lysine was lost during metabolic processes. A high efficiency of lysine utilization was also found by other authors: 89% by Libao-Mercado et al (2006) and 91% by Heger et al (2008b).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This means that 10% of the absorbed lysine was lost during metabolic processes. A high efficiency of lysine utilization was also found by other authors: 89% by Libao-Mercado et al (2006) and 91% by Heger et al (2008b).…”
Section: Resultssupporting
confidence: 72%
“…The values of lysine deposition efficiency found by Libao-Mercado et al (2006) and Heger et al (2008) show significant variations, possibly due to the methodological differences between the experiments and the premises assumed in the calculations.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a recent study using pigs raised from 10 to 25 kg body weight, Wang et al (2006) reported increases in weight gain and feed efficiency with increasing dietary thr. The increase in weight gain and feed efficiency of pigs in response to dietary thr in the present study is expected to include improved protein deposition as observed in studies reported by Zhu et al (2005) and Libao-Mercado et al (2006). Furthermore, Adeola et al (1994) observed linear increases in weights of Table 6 Estimates of relative bioavailability (RB) of tryptophan in peanut meal from daily weight gain (g/day) and gain : feed ratio (g/kg) as response criteria using supplemental dietary tryptophan concentration (g/kg), daily total tryptophan intake (g/day), or daily supplemental tryptophan intake (g/day) as independent variables ham and loin muscles in 10 kg pigs fed graded dietary levels of thr.…”
Section: Discussionsupporting
confidence: 54%
“…As discussed for other fibers in this document, increases in viscosity and concomitant decreases in digestibility have been observed with high levels of pectin and other dietary fibers, and are linked with decrease feed intake. [165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183] Thus, the impact of high levels of pectin on growth in the piglet trials is due to delayed gastric emptying and/or prolonged gut transit resulting from the viscosity of the material rather than a toxicological effect. In studies in older growing pigs (greater than 6 weeks old and older), growth effects were not observed at pectin exposures up to 6000 mg/kg bw per day, well above the exposures that impacted growth in the neonatal piglets.…”
Section: Pectinmentioning
confidence: 99%